Origin of abyssal NW atlantic water masses since the last glacial maximum - Pöppelmeier, Frerk; Blaser, Patrick; Lippold, Jörg (Paleoceanography and paleoclimatology, 2018)
Deglacial ocean circulation changes were recorded with εNd in high resolution at the abyssal Corner Rise - Distinct contribution of Northern Component Water is detectable at the abyssal northwest
First published: 07 May 2018
Gesehen am 23.04.2020